RANCANG BANGUN SISTEMPEMANTAUANDAN PEMBERIAN PAKAN UNTUK AYAMKAMPUNGBERBASIS INTERNET OF THINGS - Valgin Saputra, Al Nizar; Purnomo, Joko; Purbasari, Wika (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2025)
Local chicken farming faces challenges in terms of cage management ef iciency due to manual methods that are prone to human error and a lack of realtime monitoring. This study aims to design and develop an Internet of Things (IoT)-based automatic monitoring and feeding system for Joper local chickens. This system is designed to increase productivity and reduce waste through automation. The system integrates a DHT11 sensor for temperature and humidity monitoring, an HC- SR04 ultrasonic sensor for detecting leftover feed, an SG90 servo motor for feed distribution, a DS3231 RTC module for scheduling, and an ESP32-CAM for visual monitoring. The Gallus Feeding mobile app, developed using Flutter, allows users to monitor cage conditions and control feed distribution in real-time via the MQTT protocol. Testing was conducted based on the ISO/IEC 25010 standard, evaluating aspects of Functional Suitability, Performance Ef iciency, Usability, and Reliability. Test results showed an average system performance score of 92.71%, with Usability achieving a SUS score of 90.17 (grade A). This system has proven to improve feeding ef iciency and cage management, reduce feed waste, and support the productivity of small to medium-scale local chicken farming. This research contributes to the application of IoT technology to support SUStainable local chicken farming in Indonesia